DETERMINATION OF THE MODEL CHARACTERISTICS OF THE TRAJECTORY OF THE MOVEMENT IN CLEAN-AND-JERK USED BY FEMALE WEIGHTLIFTERS OF HIGH QUALIFICATION (Physical Culture and Sport: Scientific Perspective, 2022)
Nowadays, when information technologies have taken an important place in the training of athletes, especially in the work on technique, the problem of forming a base of model indicators of the technique of performing competitive movements by athletes has become urgent. Thanks to such data of model indicators, programmers can create specialized content that helps both the coach and the athlete to analyze their own technical actions.The article examines the competitive activity of highly qualified weightlifters and analyzes the trajectory of the barbell movement in the first push exercise - lifting the barbell to the chest.The main goal of the study was to determine the types of trajectory of barbell movements to the chest by high-class weightlifters. The research analyzed the attempts of 140 highly qualified weightlifters. As a result of the analysis of successful attempts at lifting barbells on the chest during performance at international competitions, it was possible to obtain the ratio of possession of highly qualified weightlifters of the horizontal trajectory of movement in accordance with different weight categories. As a result of the conducted research, data were obtained that show a significant advantage of the use of the first type (A) bar movement trajectory in clean-and-jerk lift by highly qualified female weightlifters. It has been defined that the second type of trajectory (B) in clean-and-jerk lift is more used by female weightlifters in lightweight categories (48-58 kg). It has been found that female athletes (53) and female athletes in heavyweight category (75+) use the third type of barbell motion trajectory (C).
Keywords: weightlift; clean-and-jerk; horizontal weights movement; trajectory types